Quality preferences and pricing of fresh-cut salads in Italy: new evidence from market data. Issue 7 (3rd July 2017) - Pilone, Vittoria; Stasi, Antonio; Baselice, Antonio
Abstract : Purpose: In Europe fresh-cut fruit and vegetables, is one of the major growing segments in agro-food sector. Current literature reports a limited number of studies about consumers' preferences towards these products. In particular, it lacks of studies focussed on fresh-cut salads and based on market data. In this paper, a study on consumer preferences towards the main attributes of Italian fresh-cut salads is proposed. More specifically the investigation is focussed on attributes assessable by consumers before purchase such as assortment, tenderness, product preparation and vegetable variety together with brand, size and type of packaging, presence of organic certification, promotion and product price. The purpose of this paper is to evaluate how much Italian consumers pay for those attributes with the aim to understand how much profitable could be different strategies in the sector. Design/methodology/approach: The analysis is based on IRI-Infoscan scanner data, consisting of 881 fresh-cut products. The impact of each attributes on pricing is measured by means of a hedonic price model. Findings: Main results show that, in Italy, fresh-cut salad price is greatly affected by tenderness, product preparation, assortment, brand, presence of organic certification, packaging attributes and vegetable variety. Practical implications: Findings offer to producers the possibility to set up products by composing the mix of attributes that gives back the highest price. In addition, they provide some insights to define manufacturer's strategies. Originality/value: This paper represents a novelty in economic literature because it can be considered an example of consumer preferences analysis towards the different attributes of fresh-cut vegetables based on real market data.